2006
DOI: 10.1093/ptj/86.2.236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetitive Shortwave Diathermy for Reducing Synovitis in Patients With Knee Osteoarthritis: An Ultrasonographic Study

Abstract: Background and Purpose. Shortwave (SW) diathermy can be used to improve vascular circulation and reduce inflammation and pain for patients with osteoarthritis. However, reduction in synovial inflammation has never been explored. The purpose of this study was to investigate whether repetitive SW diathermy, using ultrasonographic examination, could reduce synovitis in patients with knee osteoarthritis. Subjects and Methods. Thirty subjects with 44 osteoarthritic knees participated in this study. Eleven subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
2
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 18 publications
1
27
2
6
Order By: Relevance
“…PRFE therapy has shown to be beneficial in the treatment of neck pain (10,15). The treatment of osteoarthritis with PRFE has been reported to improve joint mobility and decrease pain and stiffness (16)(17)(18). Recently, there has been a focus on PRFE therapy and its application in controlling postoperative pain and in promoting the healing of chronic wounds.…”
mentioning
confidence: 99%
“…PRFE therapy has shown to be beneficial in the treatment of neck pain (10,15). The treatment of osteoarthritis with PRFE has been reported to improve joint mobility and decrease pain and stiffness (16)(17)(18). Recently, there has been a focus on PRFE therapy and its application in controlling postoperative pain and in promoting the healing of chronic wounds.…”
mentioning
confidence: 99%
“…The favourable symptomatic pain and adjunct anti‐inflammatory effect of SWD in the management of PID as reported in the present study could be associated with the effect of SWD in dilation of arterioles and capillaries that result in an increased flow of blood to the pelvic region, the dilation of capillaries also increases the exudation of fluid into the tissues followed by increased absorption these assist in the removal of waste products. These effects also help to bring about the resolution of inflammation (Goats, 1989; Rennie and Michlovitz, 1996; Haggerly and Ness, 2006; Jan et al, 2006). Chronic PID is associated with chronic pelvic pain as a result of inflammatory processes in the pelvis (EAU, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Application of SWD to the involved tissues may increase vascular circulation any changes are likely as a result of increasing tissue temperatures, which directly results in vascular dilatation, increase in pain threshold, and a decrease in pain and swelling (Hecox, 1994; Rennie and Michlovitz, 1996). Such vascular improvement also encourages resolution of the inflammatory processes by increasing nutrition, oxygen supply and by removing metabolic and waste products (Tindall, 1987; Goats, 1989) and in turn promotes natural resistance to infection (Tindall, 1987; Jan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Short‐wave diathermy is used widely by physiotherapists to alleviate certain symptoms 2 such as hampered hamstring flexibility 3 and ankle range 17 . However, the exact action of short‐waves at the cellular level is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Short‐wave diathermy (SWD) is a form of radiofrequency radiation, operating at 27.12 MHz, that is used therapeutically by physiotherapists 1–4 . For example, it is shown that hamstring flexibility can be greatly improved when SWD is used in conjunction with prolonged stretching 5 .…”
Section: Introductionmentioning
confidence: 99%